Lightning leader altitude progression in terrestrial gamma‐ray flashes. Issue 18 (18th September 2015) - Cummer, Steven A.; Lyu, Fanchao; Briggs, Michael S.; Fitzpatrick, Gerard; Roberts, Oliver J.; Dwyer, Joseph R.
Abstract Radio emissions continue to provide insight into the production of terrestrial gamma ray flashes (TGFs) by thunderstorms, including the critical question of the conditions under which they are generated. We have identified several TGF‐associated lightning radio emissions in which the altitudes of in‐cloud lightning leader pulses that precede and follow the TGF can be measured. We combine these with high absolute timing accuracy TGF observations from the Fermi satellite to determine the development of the lightning channel before, during, and after the TGF production. All of these TGFs were produced several milliseconds after the leader had initiated and when the leaders reached 1–2 km in length. After the TGFs, the leaders all continued to ascend for several more kilometers with no dramatic change in their characteristics, although they all exhibited high average velocities of 0.8–1.0 × 106 m/s. Implications in the context of TGF models are discussed. These results paint the first clear picture of the lightning processes that occur before, during, and after TGF production.